Régimen pensional y de asignación de retiro de la fuerza pública, de cara al régimen de prima media con prestación definida (2011)
This research includes comparative analysis of the requirements and amounts of old-age pensions and disability in the regime-premium solidarity with defined benefits, compared to the same elements in the allocation of retirement, invalidity pension, permanent partial disability, survivors' pension , and replacement wages in the pension plan and retirement allowance of the Colombian public forces. this research work addressed, in addition to the main objetive explain clearly and simply how to operate the complex pension system unknown to the public forces, also was demonstrated with mathematical operations, how this special regime deteriorated in the presence Dr. Alvaro Uribe Velez. Hence the urgent and profound analysis of Decree 4433 of 2004, legislation that significantly decreased the amount of disability pensions acquired in combat, and made more rigorous the requirements for the recognition of the retirement allowances of military and police.